RBD-1, a nucleolar RNA-binding protein, is essential for Caenorhabditis elegans early development through 18S ribosomal RNA processing - Saijou, Eiko (Oxford University Press, 2004)
RBD-1 is the Caenorhabditis elegans homolog of Mrd1p, which was recently shown to be required for 18S ribosomal RNA (rRNA) processing in yeast. To gain insights into the relationship between ribosome biogenesis and the development of multicellular organisms, we examined the expression and function of RBD-1. Maternal RBD-1 in the fertilized egg disappears immediately after cleavage starts, whereas zygotic RBD-1 first appears in late embryos and is localized in the nucleolus in most cells, although zygotic transcription of pre-rRNA is known to be initiated as early as the one-cell stage. RNA interference of the rbd-1 gene severely inhibits the processing of 18S rRNA in association with various developmental abnormalities, indicating its essential role in pre-rRNA processing and development in C.elegans. These results provide evidence for the linkage between ribosome biogenesis and the control of development and imply unexpected uncoupling of transcription and processing of pre-rRNA in early C.elegans embryos.